The Porous Carbon Material of Plant Feedstock as Polarization Component of the Electrodes of Supercapacitors - Z.D. Kovalyuk; S.P. Yurcenyuk; I.I. Semenchuk (Журнал нано- та електронної фізики)
This article is devoted to gradual activation technology of obtaining of nanoporous carbon material of organic feedstock of plant origin which increases specific capacity of activated carbon by 35-40 %. The main characteristics of carbonic materials were studied and established, material of plant feedstock of specific capacity of 200 F/g was obtained.